Triode type ionization vacuum gauge and pressure measurement method
By using high thermal conductivity materials to form the ion collector and appropriate support design, the problem of pressure measurement errors caused by molecular layer accumulation in the transistor ionization vacuum gauge is solved, and the accurate measurement of pressure in the vacuum chamber is achieved.
Patent Information
- Application Number
- CN201810694986.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-07-10
- Filing Date
- 2018-06-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2038-06-29
AI Technical Summary
The transistor-type ionization vacuum gauge forms a molecular layer near both axial ends of the ion collector, which makes it impossible to correctly measure the pressure in the vacuum chamber.
The ion collector is constructed with a thermal conductivity of 173W/(m·K) or above, and the design of the support member and metal material ensures that the heat of the ion collector is maintained at a high state and prevents the accumulation of molecular layers.
Accurate measurement of pressure in the vacuum chamber is achieved, and pressure measurement errors caused by the influence of the molecular layer are avoided.
Smart Images

Figure CN109238559B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to technologies such as a triode type ionization vacuum gauge. Background Art
[0002] The vacuum processing device has a vacuum chamber for film formation by sputtering, evaporation, etc. Since the pressure in the vacuum chamber has a great influence on the product yield, it is necessary to accurately measure the pressure in the vacuum chamber. -6 As a device for measuring the pressure in the Pa range, a triode type ionization vacuum gauge is known.
[0003] A triode ionization vacuum gauge generally has a hairpin-shaped (inverted V-shaped) filament, a spiral grid arranged around the filament, and a cylindrical ion collector arranged around the grid coaxially with the grid. A higher voltage (positive voltage) than the filament is applied to the grid, and a lower voltage than the grid is applied to the ion collector.
[0004] When the filament is energized, thermal electrons are radiated from the filament (near the top of the filament), accelerated toward the grid, and captured by the grid. Some of the thermal electrons collide with gas molecules scattered inside the triode ionization vacuum gauge near the grid, thereby ionizing the gas molecules.
[0005] Ionized gas molecules (positive ions) are attracted by the ion collector and collide with the ion collector, and receive electrons from the ion collector. Since the ionized gas molecules receive electrons from the ion collector, an ion current is generated in the ion collector. Since the value of the ion current is proportional to the amount of gas molecules scattered inside the triode ionization vacuum gauge, the pressure inside the object to be measured (for example, a vacuum processing device) on which the triode ionization vacuum gauge is installed can be measured by measuring the value of the ion current.
[0006] Here, as described in Patent Documents 1 and 2 below, when gas molecules (positive ions) collide with the surface of the ion collector, the gas molecules are sometimes adsorbed (e.g., physically adsorbed, chemically adsorbed) on the surface of the ion collector to form a molecular layer (physical adsorption layer, chemical adsorption layer).
[0007] The area near the center of the ion collector in the axial direction is an area with a high probability of collision of positive ions. Through continuous collision of positive ions in this area, neutral fragment molecules, neutral atoms or their ions and other particles are released from the molecular layer as much as possible. Therefore, the area near the center of the ion collector in the axial direction becomes an area where it is difficult for the molecular layer to accumulate. On the other hand, the areas near the two ends in the axial direction of the ion collector are areas with a low probability of collision of positive ions. Since positive ions do not collide continuously, they become areas where positive ions are easily accumulated into molecular layers.
[0008] In addition, as technologies related to the present application, the following Patent Documents 3 and 4 are listed.
[0009] Prior Art Literature
[0010] Patent Literature
[0011] Patent document 1: International Publication No. 2016 / 151997;
[0012] Patent document 2: International Publication No. 2016 / 139894;
[0013] Patent Document 3: Japanese Patent Application Publication No. 2006-343305;
[0014] Patent document 4: Japanese Patent Application Laid-Open No. 5-66170.
[0015] Problems to be solved by the invention
[0016] There is a problem that the pressure inside the object to be measured cannot be accurately measured due to the influence of molecular layers formed near both ends in the axial direction of the ion collector. Summary of the invention
[0017] In view of the above circumstances, an object of the present invention is to provide a triode type ionization vacuum gauge capable of accurately measuring the pressure inside a measurement object.
[0018] Solutions to Solve Problems
[0019] In order to achieve the above object, the triode type ionization vacuum gauge involved in the present invention comprises a filament, a grid, and an ion collector. The grid is arranged around the filament. The ion collector is cylindrical, arranged around the grid, and is made of a material with a thermal conductivity of 173W / (m·K) or more at 300K.
[0020] In the triode type ionization vacuum gauge, the ion collector is made of a material having a thermal conductivity of 173 W / (m·K) or more at 300 K. In other words, the ion collector is made of a material having a high thermal conductivity. As a result, the heat generated by the filament is easily transferred to the entire ion collector, and the temperature of the ion collector can be increased even near the two ends of the axial direction of the ion collector. As a result, the formation of molecular layers near the two ends of the axial direction of the ion collector can be prevented. As a result, the triode type ionization vacuum gauge can accurately measure the pressure inside the object to be measured.
[0021] In the above-mentioned triode ionization vacuum gauge, the power supplied to the filament may be 4W or less.
[0022] Here, in a small triode type ionization vacuum gauge such as one in which the power supply to the filament is set to 4W or less, the heat generated by the filament is likely to be low, so there is a problem that the temperature near the two ends of the axial direction of the ion collector is likely to be low. On the other hand, as described above, in the triode type ionization vacuum gauge involved in the present invention, the ion collector is formed of a material with high thermal conductivity. Therefore, even in a small triode type ionization vacuum gauge such as one in which the heat of the filament is likely to be low such as one in which the power supply to the filament is set to 4W or less, the temperature of the ion collector can be appropriately increased near the two ends of the axial direction of the ion collector.
[0023] The triode type ionization vacuum gauge may further include a support member. The support member supports the ion collector and is made of a material having a lower thermal conductivity than a material constituting the ion collector.
[0024] This can prevent the heat of the ion collector from being dissipated toward the support member, and the heat of the ion collector can be maintained at a high level.
[0025] The triode type ionization vacuum gauge may further include a housing portion. The housing portion is made of a metal material and houses the filament, the grid and the ion collector.
[0026] By forming the receiving portion using a metal material, it is possible to prevent charging when thermal electrons collide with the receiving portion, thereby maintaining a constant potential distribution in the space within the receiving portion. Thus, pressure can be measured with a constant sensitivity for a long period of time.
[0027] The pressure measuring method involved in the present invention comprises the following steps: preparing a triode ionization vacuum gauge, the triode ionization vacuum gauge having a filament, a grid arranged around the filament, and an ion collector arranged around the grid and made of a material with a thermal conductivity of 173 W / (m·K) or more at 300K, the ion collector being in a cylindrical shape; and measuring the internal pressure of a measured object by means of the triode ionization vacuum gauge.
[0028] Effects of the Invention
[0029] As described above, according to the present invention, it is possible to provide a triode type ionization vacuum gauge capable of accurately measuring the pressure inside a measurement object. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram showing a triode type ionization vacuum gauge according to an embodiment of the present invention as viewed from the side.
[0031] Figure 2 Schematic diagram of a triode ionization vacuum gauge viewed from above.
[0032] Figure 3 This is a graph showing the relationship between seven metal materials used as the material of the ion collector and the thermal conductivity of these metal materials at 300K.
[0033] Figure 4 The diagram shows the pressure in the vacuum chamber measured by a triode ionization vacuum gauge having ion collectors of different materials.
[0034] Figure 5 This is a schematic diagram showing the movement of positive ions that collide with the ion collector in a comparative example in which the ion collector is made of a material having a thermal conductivity of less than 173 W / (m·K) at 300 K.
[0035] Figure 6 This is a schematic diagram showing the movement of positive ions that collide with the ion collector when the ion collector is made of a material having a thermal conductivity of 173 W / (m·K) or more at 300 K. DETAILED DESCRIPTION
[0036] Hereinafter, embodiments according to the present invention will be described with reference to the drawings.
[0037] <Overall structure and structure of each part of a triode type ionization vacuum gauge>
[0038] Figure 1 This is a schematic diagram showing a triode type ionization vacuum gauge 100 according to an embodiment of the present invention as viewed from the side. Figure 2This is a schematic diagram of the triode type ionization vacuum gauge 100 as viewed from above.
[0039] As shown in these figures, the triode type ionization vacuum gauge 100 has a sensor unit 10 and a control unit 20. The sensor unit 10 has a sensor body 11 (housing portion), a filament 12, a grid 13, an ion collector 14, a plurality of terminals 15a to 15e, a grid support member 16, and an ion collector support member 17 (support member).
[0040] The sensor body 11 has a cylindrical shape having a bottom 11 c , and accommodates the filament 12 , the grid 13 , the ion collector 14 , a plurality of terminals 15 a to 15 e , the grid support member 16 , and the ion collector support member 17 therein.
[0041] The sensor body 11 has a flange 11a at the top for detachably attaching the sensor unit 10 to a measurement object such as a vacuum chamber. A groove 11b for accommodating a vacuum seal such as an O-ring is formed along the circumferential direction (θ direction) at the top and inner side of the flange 11a. The flange 11a is fixed to the measurement object such as a vacuum chamber through the vacuum seal, thereby measuring the pressure inside the measurement object using the triode type ionization vacuum gauge 100.
[0042] The sensor body 11 is made of a metal material such as stainless steel, nickel, an alloy of nickel and iron, aluminum alloy, copper, copper alloy, titanium, titanium alloy, tungsten, molybdenum, or a combination of two or more of these. The sensor body 11 is grounded.
[0043] Five terminals 15a to 15e are inserted through the bottom 11c of the sensor body 11 via an insulator (not shown). The five terminals 15a to 15e are cylindrical members that are long in the Z-axis direction. In addition, the shape of the terminal can be a triangular prism, a quadrangular prism, etc., and there is no particular limitation on the shape of the terminal. These terminals are made of metal materials such as iron, nickel, and cobalt.
[0044] Among the five terminals 15 a to 15 e , two terminals 15 a and 15 b are terminals connected to the filament 12 , one terminal 15 c is a terminal connected to the grid 13 , and the remaining two terminals 15 d and 15 e are terminals connected to the ion collector 14 .
[0045] The filament 12 is arranged near the center of the sensor body 11. The filament 12 has a hairpin shape (inverted V shape) and is formed by bending a linear member having a thickness of, for example, about φ0.1 to 0.2 mm at the center. The filament 12 may also have a linear shape, and the shape of the filament 12 is not particularly limited.
[0046] The height Hf of the filament 12 (the height of the portion of the filament 12 above the terminals 15a and 15b) is set to, for example, approximately 5 mm to 15 mm.
[0047] In the filament 12, thermal electrons are radiated from the curved top. The curved top of the filament 12 is located at the center of the grid 13 and the ion collector 14 in the axial direction (Z-axis direction) (refer to Figure 1 In addition, the top of the filament 12 is also located at the center of the grid 13 and the ion collector 14 in the horizontal direction (refer to Figure 2 ).
[0048] The filament 12 is made of a metal material such as iridium or tungsten whose surface is covered with yttrium oxide.
[0049] One end of the filament 12 is electrically and mechanically connected to the terminal 15a, and the other end is electrically and mechanically connected to the terminal 15b. In addition to serving as terminals of the filament 12, the terminals 15a and 15b also serve as support pins for supporting the filament 12 from below. In addition, in the present embodiment, the power supplied to the filament 12 is set to 4W or less.
[0050] The grid 13 is arranged around the filament 12 in a manner concentric with the filament 12. The grid 13 has a spiral shape, for example, formed by winding a linear member with a thickness of about φ0.1 to 0.3 mm into a spiral shape. In addition, the grid 13 can also be formed by punching a metal sheet or a photoetched sheet into a cylindrical shape, and the shape of the grid 13 is not particularly limited.
[0051] The height Hg of the grid 13 (refer to Figure 1 ) is set to about 10 to 30 mm, for example, and the diameter φg (refer to Figure 2 ) is set to about 5 mm to 15 mm, for example. In addition, the height Hg of the grid 13 is set to be twice the height Hf of the filament 12.
[0052] The grid 13 is made of a metal material such as tungsten, molybdenum, molybdenum whose surface is covered with platinum, tantalum, platinum, iridium, an alloy of platinum and iridium, nickel, an alloy of nickel and iron, stainless steel, or a combination of two or more thereof.
[0053] The lower end of the grid 13 is electrically and mechanically connected to the terminal 15c. In addition to serving as a terminal of the grid 13, the terminal 15c also serves as a support pin for supporting the grid 13 from below. A grid support member 16 is erected above the terminal 15c. The grid support member 16 is a member that is long in the axial direction (Z-axis direction), for example, a cylindrical member, and can abut against the inner circumference of the grid 13 and support the grid 13 from the inner circumference.
[0054] The ion collector 14 is arranged around the grid 13 in a concentric manner with the grid 13. The ion collector 14 has a cylindrical shape, and is formed by forming a plate-like member with a thickness of about 0.05 mm to 0.3 mm into a cylindrical shape. In addition, the ion collector 14 is not limited to a cylindrical shape as long as it is a cylindrical shape, and can also be formed in a square tube or the like.
[0055] The height Hi of the ion collector 14 (refer to Figure 1 ) is set to about 10 to 30 mm, for example, and the diameter φi (refer to Figure 2 ) is set to about 10 mm to 30 mm, for example. In addition, the height Hi of the ion collector 14 is set to be approximately the same as the height Hg of the grid 13 and is set to be twice the height Hf of the filament 12 .
[0056] The ion collector 14 is made of a metal material having a thermal conductivity of 173 W / (m·K) or more at 300 K. The material of the ion collector 14 can be any material as long as it has the above-mentioned properties, and metal materials such as tungsten, copper, and graphite can be used as the material. In addition, the reason for using such a material as the material of the ion collector 14 will be described in detail later.
[0057] The ion collector 14 is electrically and mechanically connected to the terminals 15d and 15e via the ion collector support member 17. The terminals 15d and 15e function not only as terminals of the ion collector 14 but also as support pins for supporting the ion collector 14 from below.
[0058] The ion collector support member 17 is electrically and mechanically connected to the terminals 15d, 15e and the ion collector 14, and is supported from below by the terminals 15d, 15e, while supporting the ion collector 14 from below. One ion collector support member 17 is provided on each of the terminal 15d side and the terminal 15e side.
[0059] The ion collector support member 17 is formed by bending a thin plate-like member along the outer periphery of the ion collector 14. In this embodiment, the ion collector support member 17 is short in the circumferential direction (θ direction), but it may be provided over the entire circumference (360°) of the ion collector 14.
[0060] The ion collector support member 17 is made of a material having a lower thermal conductivity (e.g., 300 K) than the ion collector 14. The ion collector support member 17 may be made of any material as long as it has a lower thermal conductivity than the ion collector 14, for example, a metal material such as stainless steel (SUS304), iron, nickel, or cobalt.
[0061] The control unit 20 has a housing, and a controller 21, an ammeter 22, three power supplies 23a to 23c, etc. are built in the housing. The controller 21 includes a CPU (Central Processing Unit), a volatile memory, a nonvolatile memory, and the like.
[0062] The CPU performs overall control of various parts of the triode type ionization vacuum gauge 100 according to various programs stored in the memory. For example, the CPU performs processing for controlling the operation of each power supply 23a to 23c, processing for calculating the pressure based on the ion current value measured by the ammeter 22, and processing for displaying the calculated pressure on a display (not shown).
[0063] The ammeter 22 measures the value of the ion current flowing through the ion collector 14, and outputs the measured value to the controller 21. Among the three power supplies 23a to 23c, the first power supply 23a is a power supply for passing direct current to the filament 12 to make the filament 12 red-hot, and the second power supply 23b is a power supply for applying a higher potential than the filament 12 to the grid 13. In addition, the third power supply 23c is a power supply for making the potential of the filament 12 higher than the potential of the ion collector 14.
[0064] In addition, the housing is provided with output terminals (not shown) connected to the power sources 23, and the sensor unit 10 and the control unit 20 are connected via a cable with a connector. Alternatively, the sensor unit 10 and the control unit 20 may be assembled in the same housing.
[0065] <Experiment>
[0066] Next, an experiment conducted to investigate the relationship between the thermal conductivity of the ion collector 14 and the measured pressure is described. In this experiment, seven materials were prepared as the material of the ion collector 14, and the pressure in the vacuum chamber during vacuum evacuation was measured using seven types of triode ionization vacuum gauges 100 having different materials of the ion collector 14.
[0067] Figure 3 This is a diagram showing the relationship between seven metal materials used as the material of the ion collector 14 and the thermal conductivity of these metal materials at 300K. Figure 4 Graphs showing the pressure in the vacuum chamber measured by the triode type ionization vacuum gauge 100 having the ion collector 14 made of different materials.
[0068] In this experiment, iridium whose surface was coated with yttrium oxide was used as the material of the filament 12, and the thickness of the filament 12 was set to φ0.127 mm (before being coated with yttrium oxide). In addition, the height Hf of the filament 12 was set to 10 mm.
[0069] The material of the grid 13 was molybdenum whose surface was covered with platinum, and the thickness of the grid 13 was set to 0.25 mm. The height Hg of the grid 13 was set to 20 mm, and the diameter φg of the grid 13 was set to 10 mm.
[0070] In addition, as the material of the ion collector 14, Figure 3 As shown in the figure, seven materials are used: graphite, copper, tungsten, molybdenum, nickel, platinum, and stainless steel (SUS304). Figure 3 As shown, the thermal conductivity (surface direction) of these seven materials at 300K are 700W / (m·K), 401W / (m·K), 173W / (m·K), 138W / (m·K), 90.9W / (m·K), 71.6W / (m·K), and 16W / (m·K), respectively.
[0071] Furthermore, the thickness of the ion collector 14 was set to 0.1 mm, the height Hi of the ion collector 14 was set to 20 mm, and the diameter φi of the ion collector 14 was set to 17 mm.
[0072] In addition, as the material of the ion collector supporting member 17, stainless steel (SUS304) was used.
[0073] The potential of the filament 12 was set to 25 V, the potential of the grid 13 was set to 150 V, and the potential of the ion collector 14 was set to 0 V. The power supplied to the filament 12 was set to 4 W or less, and the emission current between the filament 12 and the grid 13 was set to 1 mA.
[0074] In addition, the case where graphite, copper, or tungsten having a thermal conductivity of 173 W / (m·K) or more at 300 K is used as the material of the ion collector 14 corresponds to the embodiment of the present invention. On the other hand, the case where molybdenum, nickel, platinum, or stainless steel (SUS304) having a thermal conductivity of less than 173 W / (m·K) at 300 K is used as the material of the ion collector 14 corresponds to the comparative example.
[0075] Reference Figure 4 ,exist Figure 4 FIG. 2 shows the pressure in the vacuum chamber measured by the triode type ionization vacuum gauge 100 with different materials of the ion collector 14. Figure 4 In the figure, the vertical axis represents the measured pressure, and the horizontal axis represents the time (12 hours in total). In addition, since molybdenum, nickel, and platinum form substantially the same curve graph, they are displayed as the same curve graph.
[0076] exist Figure 4 The result is as follows: The ultimate pressure of graphite with the highest thermal conductivity (2×10 -6Pa) is the lowest. As the thermal conductivity decreases, the ultimate pressure gradually increases. The ultimate pressure of the stainless steel (SUS304) with the lowest thermal conductivity (1×10 -4 The ultimate pressure is the value when the pressure stabilizes and becomes constant after the pressure drops due to vacuum exhaust.
[0077] From this result, it can be seen that the higher the thermal conductivity, the lower the ultimate pressure. In other words, there is an inversely proportional relationship between the thermal conductivity of the ion collector 14 and the ultimate pressure.
[0078] exist Figure 4 In the present invention, we focus on two graphs related to the comparative example of the graphs corresponding to molybdenum, nickel, and platinum whose thermal conductivity at 300K is less than 173W / (m·K) and the graph corresponding to stainless steel. The pressure shown in these graphs gradually decreases as the pressure in the vacuum chamber decreases by vacuum exhaust, and when it drops to about 2×10 -5 Pa (measurement limit) and then gradually increased to about 8×10 -5 Pa, and then stabilize.
[0079] As described above, when a material with low thermal conductivity is used as the material of the ion collector 14 , the measured pressure temporarily drops and then rises to become stable at a certain constant value.
[0080] <Reasons for unstable pressure>
[0081] The reason why the pressure becomes as it is in the comparative example where the ion collector 14 is made of a material having a thermal conductivity of less than 173 W / (m·K) at 300 K will be described below. Figure 5 Schematic diagram showing the movement of positive ions 1 that collide with the ion collector 14 in a comparative example in which the ion collector 14 is made of a material having a thermal conductivity of less than 173 W / (m·K) at 300 K. Figure 5 In the figure, the grid 13 is omitted for the sake of convenience.
[0082] When the filament 12 is energized, thermal electrons are radiated from the vicinity of the top of the filament 12, and the thermal electrons are accelerated toward the grid 13 and captured by the grid 13. Some of the thermal electrons collide with gas molecules scattered inside the triode ionization vacuum gauge 100 near the grid 13, whereby the gas molecules are ionized to generate positive ions 1.
[0083] The positive ions 1 are attracted to the ion collector 14 and collide with the ion collector 14 , and receive electrons from the ion collector 14 .
[0084] Since the positive ions 1 receive electrons from the ion collector 14, an ion current is generated in the ion collector 14, and the value of the ion current is measured by the ammeter 22. Thus, the pressure inside the vacuum chamber is measured.
[0085] exist Figure 4 In the graph, the graph corresponding to stainless steel and the graph corresponding to molybdenum, nickel, and platinum are focused. In these graphs, when the pressure gradually decreases in response to the vacuum exhaust of the vacuum chamber, the gas molecules (positive ions 1) collide with the surface of the ion collector, and the gas molecules that collide with the surface form an equilibrium state: a part of them is separated as gas, and the remaining part becomes a molecular layer (for example, a physical adsorption layer or a chemical adsorption layer composed of adsorbed molecules 2).
[0086] In addition, since platinum is very stable chemically, when the ion collector 14 is made of platinum, a molecular layer generated by chemical adsorption is hardly formed compared with other examples. Figure 5 The schematic diagram of the gas molecules existing on the surface of the ion collector 14 shows the equilibrium state at a certain moment, but it can be considered that physical adsorption dominates in the molecular layer formed as a result of the collision of gas molecules (such as water molecules) with the surface of the ion collector 14.
[0087] The region near the center in the axial direction of the ion collector 14 is a region where the probability of positive ions 1 colliding is higher than the probability of forming a molecular layer generated by adsorption on the surface of the ion collector 14, and is a region where molecular layers are difficult to accumulate in a balanced state. In this region, since molecular layers are difficult to accumulate, even if positive ions 1 collide with this region, it is difficult to release particles such as neutral molecules, neutral fragment molecules, neutral atoms, or their ions.
[0088] On the other hand, since the regions near the two axial ends of the ion collector 14 have a lower collision probability with positive ions 1 than the region near the center, the molecular layer is easily accumulated over time. When the positive ions 1 collide with the accumulated molecular layer, neutral molecules, neutral fragment molecules, neutral atoms or ions thereof are released.
[0089] In addition, the energy of molecules detaching from the surface can also be considered from the temperature of molecular motion. When the ion collector 14 is viewed from this point of view, the vicinity of the center in the axial direction is a region close to the top of the filament 12 that generates heat, and thus becomes a region with high temperature (see Figure 5). Therefore, the molecular layer near the center in the axial direction of the ion collector 14 maintains a higher energy than the two ends. In other words, it can be considered that, compared with the two ends, the separation is dominant in the equilibrium state near the center, and the adsorption is dominant at the two ends. Therefore, from the perspective of the temperature of the ion collector 14, the area near the center in the axial direction of the ion collector 14 also becomes an area where the molecular layer is difficult to accumulate, and the area near the two ends in the axial direction also becomes an area where the molecular layer is easy to accumulate.
[0090] After a further period of time has passed since the vacuum exhaust of the vacuum chamber began, the composition of the gas molecules in the sensor body 11 changes toward a composition corresponding to the exhaust capacity of the vacuum chamber. Generally, gas molecules dominated by desorption are preferentially exhausted relative to adsorption, resulting in a change in the composition in which gas molecules dominated by adsorption become dominant in the vacuum chamber. For example, the composition of the gas in the sensor body 11 changes toward a composition in which water molecules that are difficult to be exhausted from the vacuum chamber are increased. Of course, the composition of the molecular layer on the surface of the ion collector 14 also changes in accordance with the change in the composition in the vacuum chamber as the measurement object.
[0091] Due to changes in the composition of gas molecules in the sensor body 11, the entire surface area of the ion collector 14 changes toward an equilibrium state where adsorption is more dominant than desorption. However, it can be said that the process of this change is slow. Figure 4 The change cannot be clearly confirmed at the time of 12h / 9, but can be confirmed during the period from 12h / 9 to 12h. In other words, it can be considered that the final equilibrium state is at the time of 12h. It can be considered that this means that the composition in the vacuum chamber changes from the normal atmospheric composition ratio to the adsorption-dominated gas composition around the time of 12h / 9.
[0092] exist Figure 4 is assumed to have a value of 1.0×10 -3 Pa or less, the vacuum exhaust system is an environment with a gas composition that exhibits an adsorption advantage. However, from the moment of opening to the atmosphere, the initial gas composition of the vacuum exhaust is not significantly different from the atmospheric composition in the initial state. In other words, the entire surface area of the ion collector 14 is in a state of equilibrium that is out of advantage, and adsorption does not develop. In other words, when Figure 4 When the tangent lines of the time change curves of various materials are understood as the values of the slopes of linear functions, all of them become negative values, so that the initial situation can be confirmed.
[0093] However, at 1.0×10 -4 When the gas composition changes below Pa, the composition of the ion collector surface 14 begins to change. Figure 4 The changes can be confirmed. Figure 4 The vacuum degree measured by other vacuum degree measuring devices is omitted in the figure, but since the value of graphite is close to the actual vacuum degree in the vacuum chamber, it should show the same vacuum degree as graphite. However, other materials show a tendency of gradually worsening vacuum degree, that is, the slope is negative but tends to zero.
[0094] This is because the composition of the surface of the ion collector 14 changes from the atmospheric composition to the gas composition with adsorption dominance, thereby changing the thickness of the molecular layer on the surface of the ion collector 14. No difference occurs before reaching this vacuum degree.
[0095] This phenomenon indicates that the temperature condition of the adsorbed surface becomes dominant compared to the previous one because the gas composition becomes the dominant one for adsorption. Figure 4 In the comparison between the materials, the material with the lower temperature surface is easy to adsorb gas molecules, and the adsorption amount, that is, the thickness of the molecular layer, increases.
[0096] Here, when the positive ion 1 collides (impacts) with the molecular layer with increasing thickness, the molecules of the molecular layer given the incident energy are separated. The detailed physical phenomenon needs further research, but from Figure 4 It can be seen from the above that, at this vacuum level, there is a proportional relationship between the amount of molecules released with respect to the incidence of positive ions on the ion collector surface of the triode ionization vacuum gauge and the thickness of the molecular layer.
[0097] That is, since the number of molecules released (detached) increases as the thickness of the molecular layer increases, the -4 Below Pa, as the equilibrium state becomes adsorption-dominated, the number of molecules detached increases, and the detached molecules are measured again by the vacuum gauge. As a result, the slope of the measured value of the vacuum degree shifts to the zero side.
[0098] Generally, adsorption / detachment stabilizes in the stage of transition to equilibrium. In other words, the moment when the slope of the measured value of the vacuum degree becomes zero is considered to be the equilibrium state of adsorption / detachment. Users of vacuum gauges recognize the moment of this equilibrium state as the measurement limit and understand it as the performance difference of the vacuum gauge. However, when the measurement limit changes over time, it is difficult to distinguish it from the original deterioration of the vacuum degree. In addition, the change itself causes users to distrust the measuring instrument, which can be said to be problematic as a product.
[0099] That is, it is necessary to avoid measuring the vacuum degree at which the slope changes from zero to a positive value, but this problem occurs in the material containing platinum. The reason is that the temperature of the surface of the ion collector 14 is low, that is, compared with other materials, the equilibrium state of separation and adsorption relative to the incident frequency of positive ions is on the adsorption side, and the molecular layer is further accumulated to increase the thickness, resulting in an increase in the amount of molecular separation caused by the incidence of positive ions.
[0100] The reason why the above slope becomes positive in the period from 12h / 9 to 12h is that in the molecular layer deposited near the two ends of the ion collector 14 in the axial direction (the position with low temperature), the molecular layer becomes a release source of molecules. That is, when the ion collector 14 is composed of various materials containing platinum, there is a problem that the pressure in the sensor body 11 becomes a locally high pressure due to the influence of the molecules released from the release source, and becomes a pressure different from the pressure in the vacuum chamber as the measurement object. Therefore, there is a problem that the pressure in the vacuum chamber cannot be measured correctly.
[0101] <Adsorbed molecules>
[0102] Next, the measurement performed to determine which type of molecules the adsorbed molecules 2 are mainly is described. In this measurement, a triode type ionization vacuum gauge having seven different materials (graphite, copper, tungsten, molybdenum, nickel, platinum, stainless steel (SUS304)) of ion collector 14 is prepared in the same manner as described above. Then, after the vacuum chamber is evacuated, the mass spectrum of the gas molecules in the sensor body 11 is measured by a quadrupole mass spectrometer when the filament 12 is turned off and when the filament 12 is turned on.
[0103] As a result, in the triode ionization vacuum gauge (comparative example) corresponding to four materials with low thermal conductivity, namely molybdenum, nickel, platinum, and stainless steel, the peak of water in the mass spectrum when the filament 12 is turned on is significantly larger than the peak of water in the mass spectrum when the filament 12 is turned off.
[0104] This indicates that the amount of water molecules scattered in the sensor body 11 when the filament 12 is on is significantly greater than the amount of water molecules scattered in the sensor body 11 when the filament 12 is off. This result indicates that the adsorbed molecules 2 are mainly water molecules.
[0105] That is, when the filament 12 is disconnected, since the water molecules do not become positive ions 1, the water molecules are not attracted by the ion collector 14, and therefore the amount of water molecules adsorbed on the ion collector 14 as adsorbed molecules 2 is small. Therefore, when the filament 12 is disconnected, since there is no release source of water molecules, the amount of water molecules scattered in the sensor body 11 is approximately the same as the amount of water molecules in the vacuum chamber, and the amount of water molecules is small.
[0106] On the other hand, when the filament 12 is turned on, water molecules become positive ions 1, and the water molecules are attracted to the ion collector 14. In addition, since the ion collector 14 is composed of a material with low thermal conductivity, water molecules are accumulated on the ion collector 14 as adsorbed molecules 2. Furthermore, since the accumulated water molecules become a release source of water molecules, the amount of water molecules scattered in the sensor body 11 becomes significantly larger when the filament 12 is turned on than when the filament 12 is turned off.
[0107] This is shown by the fact that the peak of water in the mass spectrum when the filament 12 is turned on is significantly larger than the peak of water in the mass spectrum when the filament 12 is turned off, and thus it is known that the adsorbed molecules 2 are mainly water molecules.
[0108] In the measurement here, even for platinum, which is very stable chemically, the peak of water in the mass spectrum when the filament 12 is turned on is significantly larger than the peak of water in the mass spectrum when the filament 12 is turned off. This indicates that the reason why the pressure becomes unstable in the comparative example is not the formation of a molecular layer due to chemical adsorption, but the formation of a molecular layer due to adsorption of water molecules (because platinum is difficult to form a molecular layer by chemical adsorption).
[0109] In addition, in the triode type ionization vacuum gauge 100 (this embodiment) corresponding to the three materials of graphite, copper, and tungsten having high thermal conductivity, although the peak value of water in the mass spectrum when the filament 12 is turned on is also larger than the peak value of water in the mass spectrum when the filament 12 is turned off, the difference is small. This means that in this embodiment, the amount of water molecules adsorbed when the filament 12 is turned on is much smaller than that in the comparative example.
[0110] <Functions, etc.>
[0111] As described above, in the comparative example where the ion collector 14 is formed of a material having a thermal conductivity of less than 173 W / (m·K) at 300 K, the measured pressure becomes inaccurate mainly because water molecules are adsorbed to the ion collector 14 .
[0112] Therefore, in this embodiment, in order to prevent the generation of adsorbed molecules 2 (especially water molecules), the ion collector 14 is made of a material having a thermal conductivity of 173 W / (m·K) or more at 300 K (eg, graphite, copper, tungsten).
[0113] Figure 6 Schematic diagram showing the movement of positive ions 1 that collide with the ion collector 14 when the ion collector 14 is made of a material having a thermal conductivity of 173 W / (m·K) or more at 300 K. Figure 6 In the figure, for the convenience of explanation, the grid 13 is omitted.
[0114] like Figure 6 As shown, in this embodiment, since the ion collector 14 is made of a material with high thermal conductivity, the heat generated by the transfer filament 12 can be efficiently transferred to the entire ion collector 14. Therefore, in the ion collector 14, the temperature can be increased not only in the central portion in the axial direction (Z-axis direction) but also in the vicinity of both ends in the axial direction, thereby increasing the temperature of the entire ion collector 14.
[0115] Therefore, in Figure 6 Compared with the comparative example Figure 5 On the contrary, near both ends of the ion collector 14 in the axial direction, the energy of the gas molecules that collide with the ion collector 14 as positive ions 1 for detaching from the ion collector 14 becomes high. This can prevent the generation of adsorbed molecules 2 (especially water molecules).
[0116] In addition, in the above experiment, the temperature of the ion collector 14 composed of graphite, copper, and tungsten was actually measured to be a temperature exceeding 210 degrees. Here, it can be seen that as long as the temperature of the ion collector 14 is 200 degrees or more, the adsorption of water molecules and the like can be prevented, and it can be seen that the generation of adsorbed molecules 2 can be appropriately prevented in this embodiment. In addition, in the above experiment, the temperature of the ion collector 14 (comparative example) composed of molybdenum, nickel, platinum, and stainless steel (SUS304) was actually measured to be 160° to 180°.
[0117] As described above, in this embodiment, since the generation of the adsorbed molecules 2 can be prevented, the inaccurate pressure measurement as in the comparative example can be prevented, and the pressure inside the measurement object such as the vacuum chamber can be accurately measured.
[0118] This situation manifests as Figure 4 That is, as shown in these graphs, the pressure measured in this embodiment gradually decreases as the pressure in the vacuum chamber decreases due to vacuum exhaust, and after decreasing to a predetermined value (measurement limit value), it stabilizes in this state and obtains a fixed value.
[0119] Here, in the present embodiment, the power supplied to the filament 12 is set to 4 W or less. In a small triode type ionization vacuum gauge 100 in which the power supplied to the filament 12 is set to 4 W or less, the heat generated by the filament 12 is likely to be low, and therefore, if no countermeasures are taken, there is a problem that the temperature near both ends in the axial direction of the ion collector 14 is likely to be low.
[0120] On the other hand, as described above, in the triode type ionization vacuum gauge 100 according to the present embodiment, the ion collector 14 is made of a material having high thermal conductivity. Therefore, even in a small triode type ionization vacuum gauge 100 in which the heat of the filament 12 is easily reduced, such as when the power supplied to the filament 12 is set to 4 W or less, the temperature of the ion collector 14 can be appropriately increased near both ends in the axial direction of the ion collector 14.
[0121] In this embodiment, the ion collector support member 17 is made of a material having a lower thermal conductivity than the material constituting the ion collector 14. Therefore, the heat of the ion collector 14 can be prevented from being dissipated to the ion collector support member 17, and the heat of the ion collector 14 can be maintained at a high level.
[0122] In addition, in the present embodiment, the sensor body 11 is made of a metal material. By making the sensor body 11 of a metal material, it is possible to prevent the sensor body 11 from being electrified when thermal electrons from the filament 12 collide with the sensor body 11, thereby maintaining a constant potential distribution in the space within the sensor body 11. Thus, the pressure can be measured with a constant sensitivity for a long time.
[0123] Here, in order to prevent the generation of adsorbed molecules 2 on the ion collector 14, it is conceivable to cut both ends of the axial direction (Z-axis direction) of the ion collector 14 to reduce the height Hi of the ion collector 14. However, when the height Hi of the ion collector 14 is reduced in this way, the capture efficiency of the positive ions 1 in the ion collector 14 may be reduced.
[0124] On the other hand, in the present embodiment, since the generation of the adsorbed molecules 2 can be prevented by forming the ion collector 14 with a material having high thermal conductivity, it is not necessary to reduce the height Hi of the ion collector 14. Therefore, in the present embodiment, the generation of the adsorbed molecules 2 can be appropriately prevented without reducing the capture efficiency of the positive ions 1 in the ion collector 14. In addition, as described above, in the present embodiment, the height Hi of the ion collector 14 is set to a height that is approximately twice the height Hf of the filament 12 and is the same as the height Hg of the grid 13.
[0125] In addition, this does not necessarily mean that the height Hi of the ion collector 14 must be increased. For example, the height Hi of the ion collector 14 can be made lower than the height Hg of the grid 13 .
[0126] Description of Reference Numerals
[0127] 1 positive ion;
[0128] 2 Adsorption molecules;
[0129] 10 sensor units;
[0130] 11 sensor body;
[0131] 12 Filament;
[0132] 13. Grid;
[0133] 14 ion collector;
[0134] 15 terminals;
[0135] 16. Grid support member;
[0136] 17 ion collector support member;
[0137] 20 control unit;
[0138] 100 Triode ionization vacuum gauge.
Claims
1. A triode ionization vacuum gauge having: filament; A grid disposed around the filament; an ion collector, which is cylindrical, disposed around the grid, and is made of a material having a thermal conductivity of 173 W / (m·K) or more at 300 K; and A support member supports the ion collector and is made of a material having a lower thermal conductivity than a material constituting the ion collector, wherein the support member maintains the ion collector at a temperature that prevents adsorption of water molecules.
2. The triode ionization vacuum gauge according to claim 1, wherein: The power supplied to the filament is 4W or less.
3. The triode ionization vacuum gauge according to claim 1 or 2, wherein: The device further comprises a housing part, which is made of a metal material and houses the filament, the grid and the ion collector.
4. A pressure measurement method comprising the following steps: A triode type ionization vacuum gauge is prepared, the triode type ionization vacuum gauge comprising: a filament, a grid arranged around the filament, an ion collector arranged around the grid and made of a material having a thermal conductivity of 173 W / (m·K) or more at 300 K, the ion collector being cylindrical, and a support member supporting the ion collector and made of a material having a lower thermal conductivity than the material constituting the ion collector; heating the filament so that the temperature of the ion collector is a temperature that prevents adsorption of water molecules; and The pressure inside the object to be measured is measured by the triode type ionization vacuum gauge.
Citation Information
Patent Citations
Ionization vacuum gauge
JP1993066170A
Triode-type hot cathode ionization vacuum gauge
JP2006343305A
Triode-type ionization vacuum gauge
WO2016139894A1
Hot cathode type ionization vacuum gauge
JP1990142050A
Triode type ionization vacuum gauge
WO2016151997A1